PENDAMPINGAN PERENCANAAN KENYAMANAN PADA BANGUNAN DI KELURAHAN KRENDANG, JAKARTA BARAT - Madina, Rizki Fitria; Safitri, Ristya Arinta; Sari, Christina (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2023)
Building comfort is closely related to occupant productivity. Thermal comfort is closely related to energy consumption in buildings because they are both affected by air temperature. The Community Service Team for the Architecture Department, Faculty of Civil Engineering and Planning, Universitas Trisakti was carried out in collaboration with partners, namely RW 02 Krendang Village, Tambora District, West Jakarta. RW 02 Kelurahan Krendang is in an area with medium to high density with surface cover dominated by roofs and road surfaces. Therefore, through this activity, the team provided planning assistance for comfort in buildings in the RW 02 area of Krendang Village with the aim that residents can find out alternative thermally comfortable building designs and be able to plan for them in the future independently. The method of carrying out this activity is carried out by counseling and training in calculating the material requirements for cool roofs through online, which begins with lectures and discussions in the form of questions and answers. In addition, before and after the activity the participants were given pretest and posttest as indicators of success. This is to find out the understanding of residents regarding the material presented about the concept of efforts to increase thermal comfort using a cool roof. Based on the results of the pretest, in the first question as many as 42.9% of respondents answered correctly, while in the posttest it increased to 66.7%. In the second question, the results of the pretest were 28.6% of the respondents who answered correctly and the results of the posttest were 66.7% of the respondents who answered correctly. Thus, from this activity it is known that the knowledge and understanding of the community is increasing and the awareness of residents is increasing regarding the comfort of buildings and the selection of materials that are safe for the health of residents.